AB1025 Monosodium urate crystal formations from tophi in synovial fluid. (12th June 2018) - Pascual, E.; Andrés, M.; Sivera, F.
Abstract : Background: At the joints MSU crystals form primarily at the cartilage surface; on occasions also tophi form at joint margins. Most often monosodium urate (MSU) crystals at the synovial fluid (SF) are found isolated. In tophi MSU crystals often show as spherulitic formations, fanning away from a central point 1 (Figure 1, 200x, polarised light). We have detected in synovial fluid formations of MSU crystals with an organisation indicative that they formed in tophi, draining later to the fluid. The formations also help to understand how crystals formed in tophi. Methods: Our photographic archive of SF have been reviewed. Results: Two types of formations are found. A) A spherulitic formation where the crystals fan radially as in the segment of a sphere (Figure, middle, 600x, polarised light). B) Paired crystals bound longitudinally to each other (Figure, right, 600x, phase contrast). Conclusions: At tophi spherulitic crystal formations are usual (figure 1) in which MSU crystals radiate as in a fan. A) Pieces of these same formations, seen as the segment of a sphere, are occasionally seen in SF (Figure 2), usually containing a large number of crystals and suggesting that they have drained from a tophus. Likely to build these formations, the initial crystals served as a template on which successive crystals formed by epitaxia, – the crystal formation method of least energy requirement -, explaining the rapid growth that tophi can present. Their unimpeded migration to the joint cavity suggest that they formed freely and unconnected to any organic structure within the tophus. B) In SF containing large numbers of crystals, paired crystals – two crystals lying side by side and usually of similar length and width – are also found. Their paired position likely indicates that one served as template to the other, or that they grew together sharing a crystal net – twin crystals. In all, these MSU crystal formations appear to indicate that besides the crystals formed in the surface of joint cartilages, the content of tophi can drain into the joint fluid, also contributing to the presence of crystals in it; the periarticular tophi frequently seen in ultrasound appear as the likely source for these formations. Reference: [1] Nat Rev Rheumatol. 2015;11:725. Disclosure of Interest: None declared